Results from the Pediatric European Register for Treatment of Helicobacter pylori (PERTH) - (:unkn) unknown (WILEY, 2007)
Background and Aim: Data on the eradication treatment for childhood Helicobacter pylori are scanty. A register was established on the European Society for Pediatric Gastroenterology Hepatology and Nutrition (ESPGHAN) website to collect data on treatment performed by European pediatricians to ascertain what is practiced in the field. Subjects: From January 2001 to December 2002, information on 597 children were entered by 23 European Centers, but only data of 518 treated children were completed and analyzed (86.7%, 262 male subjects, median age 9 years, range 1-14). According to their nationality, 226 children were from Southern Europe, 132 from Eastern Europe, 68 from Western Europe, and 4 from northern Europe, 68 from North Africa, and 20 from Asia. At endoscopy, 454 children had gastritis and 64 had ulcer (12.3%). Antibiotic sensitivity, tested in 361 cases, revealed 18% clarithromycin-resistant and 19% metronidazole-resistant H. pylori strains. Results: Treatment was performed for 1 week in 388 and for 2 weeks in 130 children. Antibiotics were associated with proton pump inhibitors (PPI) in 345 and with bismuth in 121 children. Triple therapy was given to 485 children, dual therapy to 26, quadruple to 7. Follow-up data, by C-13-Urea-Breath Test or histology or both, were available for 480 children. Overall eradication rate was 65.6%, significantly higher in children with ulcer (79.7%) than without (63.9%, p = .001). When given as first treatment, bismuth-containing triple therapies were more efficacious than PPI-containing ones (77% versus 64%, p = .02, OR 1.88, 95% CI 1.1-3.3). Twenty-seven different treatment regimens were used, but only six were administered to at least 18 children (range 18-157). There was no difference between treatments given for 1 or 2 weeks, or given as first or second therapies. Conclusion: European pediatricians entering data in the register used 27 different regimens. Bismuth-containing therapies resulted in higher eradication rate. Omeprazole-containing triple therapies were the most used although their efficacy was low. Therapies recommended for adults do not appear to be suitable for children.
Keywords: Helicobacter pylori; childhood gastritis; childhood ulcer; eradication treatment; antibiotic susceptibility; Bismuth salts; Proton pump inhibitor; TRIPLE THERAPY; ANTIBIOTIC-RESISTANCE; PEPTIC-ULCER; CHILDREN; ERADICATION; INFECTION; GASTRITIS; EFFICACY; MULTICENTER; ADOLESCENTS